88.7k views
3 votes
What is the rule for the transformation below?

What is the rule for the transformation below?-example-1

1 Answer

5 votes

Answer: T(-5, 3)

=================================================

Step-by-step explanation:

The translation notation T(-5, 3) looks like an ordered pair point, but it is not. Instead, it is a rule to tell you how to shift any point left/right and up/down. The first number is the left/right shifting as its done along the x axis. The negative value means we shift left, so we shift 5 units to the left. The positive 3 in the y coordinate place means we shift 3 units up.

We see this shifting happen when we go from

  • A = (-1, -1) to A ' = (-6, 2)
  • B = (2, 3) to B ' = (-3, 6)
  • C = (5, -3) to C ' = (0, 0)

The translation notation T(-5, 3) is the same as writing
(x,y) \to (x-5, y+3) which may be a more descriptive notation to use, and it would avoid confusion with ordered pair point notation.

User Manjar
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.